Integrative analysis of different low-light-tolerant cucumber lines in response to low-light stress - Li, Dandan; Yu, Fushun; Zhang, Yanzhao; Hu, Kaihong; Dai, Dongyang; Song, Siwen; Zhang, Fan; Sa, Rina; Lian, Hua; Sheng, Yunyan (Frontiers in Plant Science, 2023)
To understand the responses of different low-light-tolerant cucumber seedlings to low-light stress, the photosynthetic phenotype, RNA sequencing (RNA-seq) analysis and the expression level of photosynthesis-related genes in leaves of different low-light-tolerant lines was conducted. The results showed that there was a sharp decrease in the photosynthate accumulation in the leaves of the low-light-sensitive line, M14, resulting in a large decrease in the photosynthetic rate (Pn) (with 31.99%) of leaves compared to that of the control. However, under the same low-light treatment, there was no large drop in the low-light-tolerant line, M67, which may have been caused by damage to chloroplast ultrastructure or a decrease in chlorophyll (Chl) content. Moreover, the low expression level of genes related to photosynthesis, Chl synthesis and carbohydrate biosynthesis was another major cause for the sensitive line not being tolerant to low light. That is, the expression levels of genes CsPsbQ (the photosystem II oxygen-evolving enhancer protein 3 gene) and Csgamma (ATPase, F1 complex gene) in the M14 leaves decreased sharply (by 35.04% and 30.58%, respectively) compared with the levels in the M67 leaves, which decreased by 14.78% and 23.61%, respectively. In addition, the expression levels of genes involved in Chl synthesis and carbohydrate biosynthesis in the sensitive line (M14) decreased markedly after low-light treatment; in contrast, there were no sharp decreases or changes in the tolerant line (M67). The ability of cucumber to respond to low-light stress, as determined on the basis of the degree of damage in leaf structure and chloroplast ultrastructure, which corresponded to decreased gene expression levels and ATP phosphorylase activity, significantly differed between different low-light-tolerant lines, which was manifested as significant differences in photosynthetic capacity between them. Overall, we developed a novel analysis method to comprehensively understand the differences in phenotype and genotype of different low-light tolerant cucumber lines, the results of which provided comprehensive insight into the physiological mechanism involved in the low-light tolerance of cucumber.